The Insanity Defence In Canada, Malaysia And Singapore: A Tale Of Two Codes - Ferguson, Gerry (Journal of Malaysian and Comparative Law, 1990)
The Penal Codes in Canada and Malaysia are both based on the nineteenth century English criminal law. However, their content and their style of drafting are quite different. But the provisions for the insanity defence in both Codes are very similar, although not identical. This is hardly surprising since the insanity provisions in both Codes are modelled on the famous (and infamous) M'Naughten Rules.